Meta-analysis of the robustness of COVID-19 diagnostic kit performance during the early pandemic. Issue 4 (21st April 2022) - Shanmugam, Chandrakumar; Behring, Michael; Luthra, Vishwas; Leal, Sixto M; Varambally, Sooryanarayana; Netto, George J; Manne, Upender
Abstract : Background: Accurate detection of SARS-CoV-2 is necessary to mitigate the COVID-19 pandemic. However, the test reagents and assay platforms are varied and may not be sufficiently robust to diagnose COVID-19. Methods: We reviewed 85 studies (21 530 patients), published from five regions of the world, to highlight issues involved in the diagnosis of COVID-19 in the early phase of the pandemic. All relevant articles, published up to 31 May 2020, in PubMed, BioRiXv, MedRiXv and Google Scholar, were included. We evaluated the qualitative (9749 patients) and quantitative (10 355 patients) performance of RT-PCR and serologic diagnostic tests for real-world samples, and assessed the concordance (5538 patients) between test performance in meta-analyses. Synthesis of results was done using random effects modelling and bias was evaluated according to QUADAS-2 guidelines. Results: The RT-PCR tests exhibited heterogeneity in the primers and reagents used. Of 1957 positive RT-PCR COVID-19 participants, 1585 had positive serum antibody (IgM±IgG) tests (sensitivity 0.81, 95% CI 0.66 to 0.90). While 3509 of 3581 participants RT-PCR negative for COVID-19 were found negative by serology testing (specificity 0.98, 95% CI 0.94 to 0.99). The chemiluminescent immunoassay exhibited the highest sensitivity, followed by ELISA and lateral flow immunoassays. Serology tests had higher sensitivity and specificity for laboratory approval than for real-world reporting data. Discussion: The robustness of the assays/platforms is influenced by variability in sampling and reagents. Serological testing complements and may minimise false negative RT-PCR results. Lack of standardised assay protocols in the early phase of pandemic might have contributed to the spread of COVID-19.